Enhanced drought tolerance with artificial microRNA‐mediated StProDH1 gene silencing in potato. Issue 3 (9th April 2020) - Li, Shigui; Zhang, Ning; Zhu, Xi; Ma, Rui; Yang, Jiangwei; Tang, Xun; Si, Huaijun
Abstract: Proline is a multifunctional molecule, which especially is associated with response to abiotic stress. The proline dehydrogenase (ProDH) is the rate‐limiting enzyme in the process of proline catabolism. In the present study, two potato ProDH genes, StProDH1 and StProDH2, were cloned from potato ( Solanum tuberosum L.) cultivar 'Favorita'. Gene expression analysis indicated that these two genes exhibited tissue‐specific expression and responded differently to various stress conditions, and that the StProDH1 plays a predominant role in most of these conditions. An artificial microRNA expression vector, under the control of CaMV 35S promoter, was constructed to generate transgenic potato plants by Agrobacterium ‐mediated transformation, thereby silencing the StProDH1 gene. The result showed that the artificial microRNA caused a decline in StProDH1 expression, which was accompanied by a concomitant increase in proline content in transgenic plants under drought stress. The transgenic potato plants showed normal phenotypes under drought stress, while the non‐transgenic plants appeared withered. Results of physiological parameters assays showed that malondialdehyde, relative water content, and chlorophyll content in the transgenic potato plants were higher than that of non‐transgenic plants. Upon rehydration after two weeks of drought, proline and soluble sugar contents of the transgenic potato plants were significantly higher than those of non‐transgenic plants. These results combined demonstrate that the StProDH1 is a key player in the process of potato response to drought stress.